Proposal for Constructivist Application within the Project-Based Learning Approach for Teaching Natural Sciences: Science Fair and Laboratory Manuals - Quesada Palacios, Daniel Humberto (2024)
This essay proposes a pedagogical approach for teaching natural sciences to seventh, eighth, and ninth-grade students through project-based learning. The primary objective is to employ two instructional methodologies emphasizing laboratory experimentation and the organization of interdisciplinary scientific fairs, aimed at nurturing students' investigative and experimental skills. Adapting the guidelines from the National Program of Science and Technology Fairs to steer the scientific fair's development, and suggesting a laboratory setup approach based on the Cornell method for preliminary or optional assessment, are highlighted. Emphasis is placed on enhancing the inclusivity and assessment of students' skills in this process, alongside ensuring their engagement and active participation. The analysis concludes that there is potential for enhancing natural science teaching projects and recommends adherence to the implementation guidelines proposed herein. However, flexibility in adapting the implementation method to suit the specific needs of individual educational institutions is also acknowledged.